Queering the periphery and challenging the center: Transgender students in Israeli higher education. Issue 8 (3rd August 2021) - Tsfati, Maya; Nadan, Yochay
Abstract: This article discusses the experiences of Israeli trans students in higher education as a spatial phenomenon, demonstrating that their experiences are shaped by spatial locations – both geographic and cultural. Based on the thematic analysis of 20 in-depth interviews with Jewish Israeli transgender students from different spatial locations ('central' and 'peripheral' alike) and from varying academic fields and personal backgrounds, we maintain that trans students are engaged in a dialogue with hegemonic spatial discourses while reflecting critically on their spatial locations. The findings indicate that trans students experience periphery institutions as supportive, enabling them, through practices of collaborative activism and home-making, to create a politics from the 'margins' that displaces the 'center' as a site of inclusive queer activism. Accordingly, 'peripheral' locations enhance trans students' social activism aimed at fostering change from the 'margins', radicalizing the 'periphery', and contributing to social change. On this basis, the present study demonstrates how peripheral spatial locations contribute to queer activism by undermining homonormativity while fostering 'identification politics' that promote solidarity and collaborative practices with various social sub-groups. This sheds light on the transformative aspects of peripheral locations and their contribution to social change, expanding current knowledge on the relationship among space, gender, and activism.